Remote arts therapy in collaborative virtual environment: A pilot case study - Li, Chen; Yip, Pui Yin (Frontiers in Virtual Reality, 2023)
Motivated by the unique experience of creating three-dimensional artworks in virtual reality (VR) and the need for teletherapy due to the global pandemic, we conducted this pilot case study to explore the feasibility and effectiveness of using a custom-designed collaborative virtual environment (CVE) to enable remote arts therapy. Three participants (two females and one male) experiencing moderate to high stress as measured by the Perceived Stress Scale (PSS) joined this study. Each participant had eight 45-minute one-on-one sessions with the therapist for eight consecutive weeks. These eight sessions covered eight art creation themes and were delivered following pre-designed protocols. The CVE was the only medium to facilitate the sessions, during which the therapist and the participants were physically separated into two rooms. \textcolor{red}{The quantitative and qualitative results suggested that the CVE-enabled approach was generally feasible and was welcomed by both the participants and the therapist. However, more evidence of the approach's effectiveness in enhancing the participants' mental well-being is needed because the results of the pilot case study were affected by the pandemic.} The advantages and disadvantages of this approach and the CVE were investigated from practicality and technological affordance perspectives. Potential improvements to the CVE are also proposed better to facilitate the practice of remote arts therapy in CVE. We encourage future studies to cautiously investigate CVE-enabled remote arts therapy in clinical settings and collect more evidence regarding its effectiveness in addressing clinically diagnosed mental disorders and other complications.